Pharmacokinetics of thiamphenicol in normal and pasteurella multocida infected lactating goats - Elsayed, Mossad; Elkomy, Ashraf; Ibrahim, Faten (International Journal of Pharmacology and Toxicology, 2017)
The pharmacokinetic parameters of thiamphenicol following intravenous and intramuscular (single & repeated) administrations were estimated in normal and experimentally pasteurella multocida infected goats. Following a single intravenous injection of 30 mg thiamphenicol /kg b.wt. in normal goats, thiamphenicol could be detected therapeutically for 24 hours post intravenous injection. The serum concentration – time curve of thiamphenicol following intravenous injection showed that the drug obeyed a two compartments open model. The intramuscular bioavailability of thiamphenicol in normal goats was 66.63 %. Intramuscular injection of 30 mg thiamphenicol per kilogram body weight once daily for five consecutive days in normal and pastreulla multocida infected goats revealed a lower significant serum thiamphenicol concentration in pastreulla multocida infected goats compared with normal goats, also it’s found that: marked significant decrease in ( k1, K12, K21, T0.5(α) , T0.5(β), Tmax and CLtot in normal compared with infected goats, on the other hand a significant increase in Cmax,AUC, C0,B and β in normal compared with infected goats. Thiamphenicol was cleared by all clearance processes (Cltot) in the body at significant faster rates in Pasteurella multocida infected goats than in normal goats. The concentrations of thiamphenicol in milk were significantly lower in Pasteurella multocida infected goats than in normal goats. The mean peak urine concentrations of thiamphenicol were reached 4 hours after each intramuscular dose with a lower significant concentration in Pasteurella multocida infected goats than in normal goats.